The virulence regulator AbsR in avian pathogenic Escherichia coli has pleiotropic effects on bacterial physiology - Dongfang Zhao; Haobo Zhang; Xinyang Zhang; Fengwei Jiang; Yijing Li; Wentong Cai; Ganwu Li (Journal of Integrative Agriculture, 2024)
Avian pathogenic Escherichia coli (APEC) belonging to extraintestinal pathogenic E. coli (ExPEC) can cause severe infections in extraintestinal tissues in birds and humans, such as the lungs and blood. MprA (microcin production regulation, locus A, herein renamed AbsR, a blood survival regulator), a member of the MarR (multiple antibiotic resistance regulator) transcriptional regulator family, governs the expression of capsule biosynthetic genes in human ExPEC and represents a promising druggable target for antimicrobials. However, a deep understanding of the AbsR regulatory mechanism as well as its regulon is lacking. In this study, we present a systems-level analysis of the APEC AbsR regulon using ChIP-Seq (chromatin immunoprecipitation sequencing) and RNA-Seq (RNA sequencing) methods. We found that AbsR directly regulates 99 genes and indirectly regulates 667 genes. Furthermore, we showed that: 1) AbsR contributes to antiphagocytotic effects by macrophages and virulence in a mouse model for systemic infection by directly activating the capsular gene cluster; 2) AbsR positively impacts biofilm formation via direct regulation of the T2SS (type II secretion system) but plays a marginal role in virulence; and 3) AbsR directly upregulates the acid tolerance signaling system EvgAS to withstand acid stress but is dispensable in ExPEC virulence. Finally, our data indicate that the role of AbsR in virulence gene regulation is relatively conserved in ExPEC strains. Altogether, this study provides a comprehensive analysis of the AbsR regulon and regulatory mechanism, and our data suggest that AbsR likely influences virulence primarily through the control of capsule production. Interestingly, we found that AbsR severely represses the expression of the type I-F CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR associated) systems, which could have implications in CRISPR biology and application.